2003
DOI: 10.1068/p5036
|View full text |Cite
|
Sign up to set email alerts
|

Children's Search for Targets Located within and beyond the Field of View: Effects of Deafness and Age

Abstract: The localisation time of visual targets within and beyond the field of view and the relative timing of the onsets of eye and head movements were examined in deaf and hearing children of two age groups: 5-7 years and 10-12 years. Compared to their hearing peers, the deaf children showed more often a mode of eye-head coordination in which the head leads the eye. The discrepancy between the onsets of eye and head movements were greater for the younger than for the older groups. Furthermore, the deaf children took… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
2
6
0
Order By: Relevance
“…Control children were matched for age and sex. In particular, the age factor is of relevance here because in the aforementioned study (Netelenbos and Savelsbergh 2003) of children from 5 to 12 years old, we found a clear significant effect for age on localization time.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Control children were matched for age and sex. In particular, the age factor is of relevance here because in the aforementioned study (Netelenbos and Savelsbergh 2003) of children from 5 to 12 years old, we found a clear significant effect for age on localization time.…”
mentioning
confidence: 74%
“…We examined visual search behaviour by means of apparatus used in previous research (Netelenbos and Savelsbergh 2003). This ring-shaped apparatus, which surrounds the child, made it possible to present visual targets within and beyond the initial field of view.…”
mentioning
confidence: 99%
“…No differences were observed in visual sustained attention [102]. However, young deaf children were more likely to be distracted by peripheral information than hearing children (before the age of 9) [102], and at ages of 5-12 years, deaf children used slower visual search strategies [103]. Notably, the selection criteria for participants in the deaf population play a major role in determining the effects, particularly regarding the degree of hearing loss/auditory simulation.…”
Section: Adaptation To Auditory Deprivationmentioning
confidence: 99%
“…Seven non-injured children, matched for age and sex, participated in the study: four right-hemisphere lesion control children (mean age 8 years 8 months, SD 1 year 9 months), three left-hemisphere lesion control children (mean age 9 years 1 month, SD 3 months). The control children were chosen from 50 primary school children who had participated in a previous study (Netelenbos and Savelsbergh 2003). The localization study and standard psychometric tests were performed by the second author.…”
Section: Participantsmentioning
confidence: 99%